Determination of coordinates of the earthquake hypocenter with a known structure of the earth's crust - T. G. Aslanov; Yu. A. Sidorkina (Вестник Дагестанского государственного технического университета: Технические науки, 2022)
Objective. The aim of the study is to develop methods for determining the coordinates of the hypocenter of an earthquake with a known structure of the earth's crust. Method. To solve the problem, the brute force method, the confidence interval, the comparative method and the enumeration of possible options on the grid are used. Result. A method has been developed for determining the coordinates of an earthquake source with a known structure of the earth's crust using points of various figures of the n-th order as geometric locations in calculations. Conclusion. The proposed method, with the known structure of the earth's crust, makes it possible to use all known methods that require information on the travel time differences of seismic waves to spaced seismic sensors and the difference in travel times of longitudinal and transverse seismic waves to the seismic sensor for calculating the coordinates of the earthquake hypocenter. The accuracy of determining the coordinates of the earthquake hypocenter depends on the quality of determining the structure of the earth's crust on which the seismic event was observed.